2021
DOI: 10.3390/molecules26175135
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Chemistry Applied to the Design of N-Acyl Homoserine Lactone Analogues as Bacterial Quorum Sensing Signals Mimics

Abstract: N-acyl homoserine lactones (AHLs) are small signaling molecules used by many Gram-negative bacteria for coordinating their behavior as a function of their population density. This process, based on the biosynthesis and the sensing of such molecular signals, and referred to as Quorum Sensing (QS), regulates various gene expressions, including growth, virulence, biofilms formation, and toxin production. Considering the role of QS in bacterial pathogenicity, its modulation appears as a possible complementary appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Surfaceimmobilized QSIs block bacterial communication and affect the formation of biofilms on the surface of biomaterials [194,195]. It has been found that furanone is a substance with a similar structure to N-acyl homoserine lactone (AHL), a signal molecule of gramnegative bacterial QS, which competes with AHLs for receptors, thus interfering with QS to inhibit biofilms [196]. The intergeneric quorum-sensing signal molecule autoinducer-2 (AI-2) of F. nucleatum is very important for the development of pathogenicity and biofilm formation [197].…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Surfaceimmobilized QSIs block bacterial communication and affect the formation of biofilms on the surface of biomaterials [194,195]. It has been found that furanone is a substance with a similar structure to N-acyl homoserine lactone (AHL), a signal molecule of gramnegative bacterial QS, which competes with AHLs for receptors, thus interfering with QS to inhibit biofilms [196]. The intergeneric quorum-sensing signal molecule autoinducer-2 (AI-2) of F. nucleatum is very important for the development of pathogenicity and biofilm formation [197].…”
Section: Chemical Modificationmentioning
confidence: 99%
“…AHL analogues have been synthesized to competitively bind to AHL receptor molecules, effectively obstructing the QS system and inhibiting biofilm formation. , Various AHL analogues have been designed using three primary approaches: (i) maintaining the homoserine lactone ring of the AHL structure while introducing substituents in the acyl side chain; (ii) keeping the acyl side of the AHL structure unaltered and introducing substituents in the homoserine lactone ring; and (iii) simultaneously modifying both the homoserine lactone ring and the acyl side chain of AHL. In the past decade, numerous strategies have been employed to modify AHL. , Examples include substituting the homoserine lactone ring with various functional groups (such as thiazolidinone, cyclohexanone, and thiolactone ring), introducing heteroatoms into the amide position, increasing unsaturation in the acyl side chain, and modifying the structure of the acyl side chain. These modifications are aimed at enhancing the QSI activity of AHL or mitigating its susceptibility to hydrolysis. For instance, in P. aeruginosa , the AHL analogue meta-bromo-thiolactone induces conformational changes in LuxR receptors, weakens their interaction with RNA polymerase, and reduces their transcriptional activation potential. , Consequently, this inhibits the expression of virulence factor genes and prevents biofilm formation.…”
Section: Qs and Qsismentioning
confidence: 99%
“…In the past decade, numerous strategies have been employed to modify AHL. 99,100 Examples include substituting the homoserine lactone ring with various functional groups (such as thiazolidinone, cyclohexanone, and thiolactone ring), introducing heteroatoms into the amide position, increasing unsaturation in the acyl side chain, and modifying the structure of the acyl side chain. These modifications are aimed at enhancing the QSI activity of AHL or mitigating its susceptibility to hydrolysis.…”
Section: Autoinducer Analogues Ahl Analoguesmentioning
confidence: 99%
“…QS controls various important features in bacteria: virulence, motility, growth, biofilm, proteases, and elastase, among others making it a pilar in most bacterial features [ 263 ]. This signaling molecule is composed of two major components: one homoserine lactone ring and a fatty acid sidechain, also known as an acyl chain [ 264 ]. Anti-virulence drugs can be used alone or in combination with antibiotics and their target, unlike antibiotics, is not to kill the bacteria but to prevent or inhibit its capacity to cause an infection [ 265 ].…”
Section: Quorum-sensing Inhibitorsmentioning
confidence: 99%